The Croatian Standardisation of the MMPI-A - Matešić, Krunoslav (Array, 2005)
The aim of the work was to calculate the norms for the Minnesota Multiphasic Personality inventory for Adolescents ona a Croatian Sample. The purpose of the MMPI-A inventory is to detect psychopathology and assist in identifying personal, social and behavioural problems in adolescents. The inventory consists of 478 items yielding scales divided into 6 groups. The normative sample of adolescents was made up of 382 males and 380 females aged between 14 and 18 years. The clinical sample included 38 males and 68 females in the same age range. Both were regionally representative samples. Norms were calculated from the results collected in the normative sample, i.e. raw score conversion talbes from individual scales to uniform or linear t-scores. The uniform transformation of t-scores was used to establish the equivalence of percentiles in different MMPI scales. Factor analysis of MMPI-A basic scales revealed 4 factors, which is in conjunction with the most common factor structure of standardisations in the US and elsewhere.